3 - Resources, Population and Conflicts: Two African Case Studies*: 10.4314/ad.v24i3.22126 - Obi, Cyril (Africa Development, 1999)
This article critically analyses the complex linkages between population, resource insecurity and conflict. It argues that rapid population growth beyond the limits of the 'carrying capacity' of the eco-system and resource scarcities cannot alone be the cause of conflict. Rather, issues of the distribution of resources, power, and the linkage between the modes of production and the contradictions embedded in social relations are the fundamental causes of conflict. Using two cases: that of the conflict between the Ogoni, and Shell and the ecological dimensions of the Sudanese civil war, it is shown that the state in Africa is not just a mediator of conflict, but is an actor in conflict, repressing its own citizens, alienating them, and blocking their access to resources, at the behest of global capitalist interests and those of local elites. Thus, conflicts over the control of resources—power—tend to be defined more by access to the means of violence, state power, and the survival of the people.